Exploring Differences in Demographic Profiles and Digital Footprint Awareness between Private and Public-School Students: A Comparative Study - Cris Norman P Olipas (East Asian Journal of Multidisciplinary Research, 2023)
The objective of this study was to contrast the digital footprint awareness and demographic characteristics of college students enrolled in private and public higher education institutions (HEIs) in the Philippines. Using a quantitative descriptive research design, the study collected data from 497 respondents from both types of institutions during the first semester of the academic year 2022-2023. The research instrument was adopted from a previous study but modified to fit the context of this study. The instrument underwent content and face validity measures to ensure that it was valid. Results showed that there were no significant differences in digital footprint awareness between the respondents from private and public HEIs. The study offered valuable insights into the similarities and distinctions in digital footprint awareness among college students in private and public higher education institutions in the Philippines. The study recommended further research on the factors that affected digital footprint awareness, such as social media use and online behavior. Additionally, the study suggested the development of educational programs and campaigns to raise awareness about digital footprints and cybersecurity among college students.